1988
DOI: 10.1007/bf01805526
|View full text |Cite
|
Sign up to set email alerts
|

Transient neonatal tyrosinaemia

Abstract: Children who had presented with transient neonatal tyrosinaemia (TNT) were compared with a group of unaffected controls at 7-9 years of age. A comprehensive psychometric assessment revealed significant differences between the groups in adaptive behaviour, psycholinguistic abilities, and speed of learning. In nearly all components of the tests used, higher levels of TNT were associated with lower levels of performance. This study demonstrates that TNT, a condition commonly regarded as benign in the short term, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
1
16
0
Order By: Relevance
“…3 We found that when studied at 15 months of age 4 and again between 7 and 8 years of age, high tyrosine infants had a significantly lower performance IQ than low tyrosine infants. 5 In our infants, there was no significant correlation between gestational age and psychometric performance; in fact, when grouped according to birth weight, the most significant correlation between psychometric abnormalities and tyrosine levels was found in infants with birth weight greater than 2000 g. Our conclusions were subsequently confirmed by Mamunes et al 6 and Rice et al 7 Unfortunately, much of this work has been forgotten with the passage of time.…”
supporting
confidence: 63%
“…3 We found that when studied at 15 months of age 4 and again between 7 and 8 years of age, high tyrosine infants had a significantly lower performance IQ than low tyrosine infants. 5 In our infants, there was no significant correlation between gestational age and psychometric performance; in fact, when grouped according to birth weight, the most significant correlation between psychometric abnormalities and tyrosine levels was found in infants with birth weight greater than 2000 g. Our conclusions were subsequently confirmed by Mamunes et al 6 and Rice et al 7 Unfortunately, much of this work has been forgotten with the passage of time.…”
supporting
confidence: 63%
“…Most patients with transient tyrosinemia have no complications or long-term effects from a short period of high plasma tyrosine. 1,2 However, Rice et al 6 *Formula recipe: 2 cup (60 g) Shaklee Slim Plan powder with 1 tsp olive oil and enough water to make 20 oz per batch. Formula intake: averaged 5 oz every 4 hours or 30 oz every 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Fois et al [9] also described three normal children born to a mother with mild hypertyrosinaemia, while Hyanek et al [16] documented normal outcome in two pregnancies of a mother with mild tyrosinaemia type II who had minimally elevated plasma tyrosine (232 gmol/1) and a phenylalanine level in the upper normal range (64 ~tmol/1). Infants who have suffered transient neonatal tyrosinaemia have been shown subsequently to have difficulty with a range of psychometric tests [21], although these problems may simply reflect an increased incidence of other pathologies in these infants. In rats, mild elevations in plasma tyrosine (150-360 txmol/1) induced by dietary tyrosine supplementation during pregnancy have been shown to result in learning difficulties in offspring [18].…”
Section: Discussionmentioning
confidence: 99%